OPTIMALISASI PEMBIAYAAN MUSYARAKAH UNTUK PENGUATAN USAHA MIKRO KECIL - Irsyad Kurniawan Widjanarko; Muhammad Bobby Hafidz; Nurlabibah Elsyia Jundiah; Erlina Salsa Anjani (Media Riset Bisnis Manajemen Akuntansi, 2025)
Musyarakah financing is a strategic tool to empower Micro and Small Enterprises (MSEs) through justice, collaboration, and profit-sharing based on Islamic principles. This study explores the implementation of musyarakah contracts in MSEs, identifies existing challenges, and proposes optimization strategies. Through a literature review, the study reveals that while musyarakah provides fair, interest-free financing, its application is limited by low Islamic financial literacy, weak oversight, and limited technological and managerial capabilities among MSE actors. Despite these issues, musyarakah plays a vital role in expanding access to capital, improving business practices, and strengthening MSEs' position in the national economy. Optimization can be achieved through enhanced education, stronger and sustainable partnerships, simplified regulations, and digital integration. With these improvements, musyarakah has strong potential to serve as an inclusive, sustainable instrument aligned with Islamic economic values, contributing significantly to the growth and resilience of the MSE sector.Keywords : Islamic Finance, Micro and Small Enterprises, Musyarakah.